Disturbed theta and gamma coupling as a potential mechanism for visuospatial working memory dysfunction in people with schizophrenia. Issue 1 (December 2016) - Lynn, Peter; Sponheim, Scott
Abstract Working memory (WM) deficits have been repeatedly observed in people with schizophrenia (PSZ) and their unaffected biological relatives (REL). Given the apparent association with genetic liability for schizophrenia, WM deficits have been proposed as a potential endophenotype for the disorder. Abnormal neural responses during WM performance have likewise been observed in PSZ and REL and may reflect the expression of genetic liability for schizophrenia in brain function. Relatively recent investigations have examined the role of neural oscillatory activity during visuospatial WM function in healthy people, as well as dysfunction in psychopathology. This research was in part motivated by a neural model of WM proposed by Lisman and Idiart (Science 267:1512–1515, 1995) that delineated a mechanism for representing multiple stimuli within WM through systematic interactions between neural oscillations in the theta- and gamma- frequency ranges. Aberrant oscillatory activity in theta and gamma frequency ranges has since been proposed as a potential underlying factor in WM dysfunction in PSZ and REL. The experimental evidence derived from studies of healthy people that pertains to the theta-gamma model of WM is reviewed herein. Although scarce, direct examinations of theta-gamma interactions in PSZ and REL are likewise reviewed in addition to reports of separate deficits in theta and gamma frequencies observed in PSZ during WM. The implications of theta and gamma oscillatory deficits reported in PSZ are discussed in the context of the Lisman and Idiart (Science 267:1512–1515, 1995) model, as well as how these deficits may result in aberrant theta-gamma interactions that give rise to visuospatial WM dysfunction. Given evidence supporting the Lisman and Idiart (Science 267:1512–1515, 1995) model of theta-gamma interactions in WM and the lack of direct exploration of the model in schizophrenia, there is an imperative to carry out formal testing of theta-gamma interactions in PSZ and REL during WM.